2012
DOI: 10.1111/j.1442-9993.2011.02344.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting change in an Australian flowering record: Comparisons of linear regression and cumulative sum analysis change point analysis

Abstract: Linear regression and cumulative sum analysis (CUSUM) change point analyses were used to determine whether there had been a significant change in the first flowering date between 1983 and 2006 for 65 species. Both methods agreed that the first flowering date of 47 species did not change and that eight species had a significant change (P < 0.05) in their flowering. Three species shifted to later flowering and five species to earlier. Over the observation period, each method found that the average shift to later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Also, Bayesian techniques allow surmounting the pitfalls of linear regression (Dose and Menzel, 2004, Mendoza et al unpublished) and can be especially helpful for detecting change points and rates of these changes in long-term series (Schleip et al, 2008). However, we warn that different statistical methods applied to phenology are typically not interchangeable and they can show differences in rates of change or even species responses (Keatley and Hudson, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Bayesian techniques allow surmounting the pitfalls of linear regression (Dose and Menzel, 2004, Mendoza et al unpublished) and can be especially helpful for detecting change points and rates of these changes in long-term series (Schleip et al, 2008). However, we warn that different statistical methods applied to phenology are typically not interchangeable and they can show differences in rates of change or even species responses (Keatley and Hudson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This complexity implies temporal autocorrelation, non-linearity, non-stationary properties (which means that time series can vary over time), and an excess of zeros due to the frequent non-occurrence of the phenophase of interest. Some of the possibilities for overcoming such problems include the use of Cumulative Sum Analysis (CUSUM) for detecting change-point in phenological data (Keatley and Hudson, 2012), Generalized Additive Models for Location, Scale and Shape (GAMLSS) Polansky and Boesch, 2013), cross-correlations (Wright and CalderĂłn, 2006), and their extension by means of wavelet cross-correlations of bivariate time series (Hudson et al, 2011). Although these methods are rarely used in tropical studies, they ensure that drivers of phenology can be identified from multiple predictors and account for the non-linearity of time series and their complexity.…”
Section: Discussionmentioning
confidence: 99%
“…oxysporum , which may represent the situation in nature, can accelerate flowering time in Arabidopsis. Evidence suggests that global warming has already affected the flowering time of many plant species [ 96 – 98 ]. Simulated future seasonal warming accelerated flowering and even prompted switching of life history strategies from ‘winter’ to ‘rapid cycling’ in A .…”
Section: Discussionmentioning
confidence: 99%
“…Current trends of rising maximum and mean temperatures decreases in rainfall along the coasts (expect from the northern coast) and cloud cover (i.e. leading to increasing solar exposure) [ 56 ], will continue to result in phenological shifts in Australia [ 5 , 14 , 35 ], as has been documented in northern hemisphere [ 2 , 36 ]. Average temperatures in all stations sampled in this study for example, will increase by approximately 3°C and the number of extreme hot days (>35°C) will double or triple by 2090 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%